Immunological Changes and Complement Proteins in Major Thalassemia Patients Proteins Post-Splenectomy: Perubahan Imunologi dan Protein Komplemen pada Pasien Talasemia Mayor Protein Pasca-Splenektomi - Eman A. Mizher (Academia Open, 2024)
Background: Thalassemia is one of the most prevalent genetic disorders worldwide, with infections being a leading cause of mortality due to compromised immune function. Specific Background: Prior studies suggest that major thalassemia patients are highly susceptible to microbial infections, possibly due to altered immunological profiles, particularly immunoglobulin (IgG, IgM) and complement (C3, C4) levels. Knowledge Gap: However, the specific immunological changes pre- and post-splenectomy in these patients remain underexplored. Aims: This study aims to assess the levels of immunoglobulins (IgG and IgM) and complement proteins (C3 and C4) in major thalassemia patients both before and after splenectomy compared to healthy controls. Results: Our analysis of 50 thalassemia patients (34 males, 16 females) and 30 healthy individuals revealed that thalassemia patients exhibited significantly lower levels of C3 and C4 (88.52±24.49, 21.20±6.66) compared to healthy controls (123.50±19.04, 32.87±9.77). IgG and IgM were elevated in patients (1288.12±467.87, 153.46±51.29) compared to controls (1129.93±295.96, 148.67±50.17). Post-splenectomy, patients showed a significant decline in IgG (1001.56±154.14) and IgM (110.08±25.83) levels, along with further decreases in C3 (83.28±24.13) and C4 (17.48±4.86). Novelty: This study provides novel evidence of the immunological shifts in thalassemia patients post-splenectomy, demonstrating significant reductions in both immunoglobulins and complement proteins, thereby elevating the risk of infection. Implications: These findings highlight the spleen's crucial role in maintaining immune competence and suggest that splenectomy in thalassemia patients requires careful post-operative immune monitoring to mitigate infection risks. Highlights: Splenectomy lowers IgG, IgM, C3, and C4 levels in thalassemia patients. Post-splenectomy patients face higher infection risk due to immune weakening. Highlights spleen's crucial role in immune defense for thalassemia patients. Keywords: Thalassemia, Splenectomy, Immunoglobulins, Complement Proteins, Immune Competence